Stimulating the discussion on saliva substitutes: a clinical perspective. (30th January 2013) - Dost, F; Farah, CS
Abstract Xerostomia is a significant problem commonly faced by patients and oral health practitioners. There is no cure for this condition, which commonly manifests as a side effect of medications, head and neck irradiation and other systemic conditions, such as Sjögren's syndrome and type 2 diabetes. It may also arise idiopathically. Therefore, treatment is palliative and takes the form of oral lubricants and saliva substitutes which aim to reduce symptoms associated with xerostomia as well as prevent oral disease secondary to it. Recently there has been an expansion of the number and range of products available in Australia for the palliative management of xerostomia. It is imperative then that oral health professionals have a sound understanding of the advantages and disadvantages of using such products as patients tend to be well informed about new products which are commercially available. This article discusses some of the most commonly available products used for the symptomatic relief and preventive management of xerostomia. Amongst the plethora of products available to the patient suffering from xerostomia, no single product or product range adequately reproduces the properties of natural saliva and therefore consideration of patients' concerns, needs and oral health state should be taken into account when formulating a home care regime. With Australia's ageing population and its heavier reliance on medications and treatments which may induce xerostomia, oral health professionals are likely to encounter this condition more than ever before and therefore an understanding of xerostomia and its management is essential to patient care.